Foreign bodies in the tracheobronchial tree in adults - Pawełczyk, Konrad; Marciniak, Marek; Kacprzak, Grzegorz; Porębska, Irena; Kołodziej, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : The inhalation of foreign bodies in adults is less common than in children, however, in some cases it may constitute a serious clinical problem. The aim of the study was to evaluate the circumstances of aspiration, methods of treatment and respiratory complications. Material and methods : The retrospective review encompassed 29 709 bronchoscopies performed between 1999 and 2009 in the Lower Silesian Centre of Lung Diseases in Wrocław. Results : Forty-three cases of foreign body inhalation were identified. In the majority of patients (69.8%), aspiration was suspected prior to admission, with risk factors being present in 11 (25.6%). There were four out-patients (9.3%). The time of hospitalization was longer in the group of patients with an unsuspected foreign body (mean 9.6 days) than in the group of patients with a known history of aspiration (mean 4 days). The foreign bodies were removed by flexible bronchoscopy (37.2%), rigid bronchoscopy (55.8%) or thoracotomy (7%). Granulation tissue was observed in most of the patients in whom diagnosis was made more than one week from aspiration (17/21 – 81%) and in only two patients with the aspiration to admission time of less than one week (2/22 – 9%). Four patients needed further hospitalization due to complications. They were successfully treated endoscopically with argon plasma coagulation or with antibiotics and made a full recovery. Conclusions : In cases of persistent symptoms from the respiratory tract, in patients with risk factors, foreign body aspiration should be considered. Interventional bronchoscopy should be performed as soon as possible to prevent complications. Thoracotomy is rarely necessary. Even in cases of complications, further course of the disease is uneventful.